The Use of Technology to Assist School-Aged Students with High Incidence Special Needs in Reading - Maria Earman Stetter (MDPI AG, 2018)
This paper delineates some of the ways students with high incidence special needs are currently being served with technology in the United States in K–12 to learn skills or accomplish tasks related to reading. Categories examined were read aloud tools, computer applications, traditional instructional methods that utilized technology, and online instructional environments. The categories examined in online instructional environments include the prevalence of students with special needs, how Individual Education Plan requirements, such as accommodations and modifications, are being addressed, parental participation, and concerns in the online environments. Suggestions for future work at the intersection of reading technology and teachers of students with special needs are included, as well as conclusions from the current work. Future work with teachers of students with special needs is required to help better serve their unique learning requirements.